2013
DOI: 10.17221/77/2012-pps
|View full text |Cite
|
Sign up to set email alerts
|

Anastomosis grouping of Rhizoctonia solani and binucleate Rhizoctonia spp. isolated from pepper in Erzincan, Turkey

Abstract: Tuncer S., Eken C. (2013) [2007][2008]. The most prevalent multinucleate anastomosis groups (AG) were AG-4 (85.2%), followed by AG-2 type 1 (7.4%), AG-6 (5.0%), and AG-3 (2.5%). The population of binucleate Rhizoctonia spp. comprised AG-A (82.4%), AG-K (11.8%), and AG-G (5.9%). Rhizoctonia solani AG-3 and AG-6, as well as binucleate Rhizoctonia spp. AG-G and AG-K on pepper (c. annuum) were firstly determined in this study. During both in vitro and in vivo pathogenicity experiments differences in virulence lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…In another study, isolates of R. solani AG-4 were recovered from infected winter squash plants grown in the Black Sea region (ERPER et al, 2015). However, in Turkey, isolates of AG-1, AG-2 type 1, AG-3, AG-4, AG-5, AG-6, AG-9, AG-10 and AG-11 of R. solani and AG-A, AG-E, AG-F, AG-G, AG-I and AG-K of BN Rhizoctonia were previously detected on bean and pepper plants in different regions of Turkey (DEMIRCI;DOKEN, 1995;DEMIRCI, 2004;TUNCER;EKEN, 2013). In addition, Misawa and Kuninaga (2010) identified foot rot caused by R. solani AG-2-1 and AG-3 on mature tomato plants in Hokkaido, Japan. Similarly, other researchers reported that Rhizoctonia group fungi were detected on 264 Characterization and pathogenicity… YILDIRIM,E.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In another study, isolates of R. solani AG-4 were recovered from infected winter squash plants grown in the Black Sea region (ERPER et al, 2015). However, in Turkey, isolates of AG-1, AG-2 type 1, AG-3, AG-4, AG-5, AG-6, AG-9, AG-10 and AG-11 of R. solani and AG-A, AG-E, AG-F, AG-G, AG-I and AG-K of BN Rhizoctonia were previously detected on bean and pepper plants in different regions of Turkey (DEMIRCI;DOKEN, 1995;DEMIRCI, 2004;TUNCER;EKEN, 2013). In addition, Misawa and Kuninaga (2010) identified foot rot caused by R. solani AG-2-1 and AG-3 on mature tomato plants in Hokkaido, Japan. Similarly, other researchers reported that Rhizoctonia group fungi were detected on 264 Characterization and pathogenicity… YILDIRIM,E.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the study, R. solani AG-4 was found as the most prevalent anastomosis group (97.9%). Additionally, Tuncer and Eken (2013) found that more than three quarters of the 81 R. solani isolates obtained from peppers grown in Erzincan province, Turkey belonged to AG-4. Alike, the most common occurrence of R. solani AG-4 isolates on cucumber, pepper and snap bean plants has also been reported from other countries by several workers (MIRMAJLESSI et al, 2012;HARATIANA et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations